"Murmur Beyond Silence" by Eugen D. Popin. Between Heart and Intellection, Past and Present - K. V. Twain (Eon, 2022)
In his latest poetry volume, Murmur Beyond Silence, Eugen D. Popin offers us a mythico-religious literary journey through some of the essential spheres of life (nature, family, love), as well as poetic commentaries on Romania's communist regime and the war now being waged against the human species. The volume was published in Romanian in 2021 and in English in 2022.